Pengaruh Ukuran Perusahaan dan Good Corporate Governance Terhadap Corporate Social Responsibility pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Wuryanti, Lestari; Indriani, Wiewiek; Sari, Nita Permata (Universitas Malahayati, 2021)
Purpose of this study to explain how much the company and good corporate governancecan affect corporate social responsibility. Data was collected by targeting randomsampling from 12 food and beverage companies listed on the Indonesia Stock Exchangebetween 2016-2020. Multiple linear analysis was used as the analysis method. Thentested the hypothesis with a partial T test and simultaneous F test with the determinantcoefficient with a significance level of 5%. The size of a company does not have asignificant impact on changes in the social responsibility of a company. The personalresponsibility of an organization does not significantly affect the changing socialresponsibility of a company. Ownership does not have a significant impact on changesin the social responsibility of a company. The board of directors has a decisive impacton the changing social responsibility of a company. However, based on simultaneousboard reviews, the combination of management ownership, organizational ownership,and firm size has a significant impact on corporate social responsibility.Keyword: Corporate Social Responsibility, Company Size, Institutional Ownership,Managerial Ownership, Board of Directors